Gazing the dusty mirror: Joint effect of narcissism and sadism on workplace incivility via indirect effect of paranoia, antagonism, and emotional intelligence - Wang, Bo; Fiaz, Muhammad; Hayat Mughal, Yasir; Kiran, Alina; Ullah, Irfan; Wisetsri, Worakamol (Frontiers in Psychology, 2022)
Workplace productivity is badly affected by many negative factors such as narcissism, and sadism. In addition, paranoia and antagonism play an important role in increasing workplace incivility. Through emotional intelligence, such negative behaviors could be addressed by managers and their junior colleagues. The current study aims to investigate the parallel mediating role of paranoia, antagonism, and emotional intelligence on the relationship between narcissism, sadism, and workplace incivility. A survey approach was used. Primary data was collected in PLS-SEM. The population of the study was all faculty members in higher education institutions in the Khyber Pakhtunkhwa (Pakistan) region. A measurement model and structural model were developed. The measurement model demonstrated that convergent and discriminant validities were established. The structural model's findings revealed that narcissism, antagonism, and emotional intelligence were not mediated between narcissism and workplace incivility. Similarly, emotional intelligence did not play any mediating role between sadism and workplace incivility. This implied that emotional intelligence has no role in decreasing or reducing workplace uncivil behavior.